Democracy's third wave and national defense spending - Johannes Blum (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
I investigate how the third wave of democracy influenced national defense spending by using a panel of 110 countries for the period 1972-2013. I use new SIPRI data on military expenditure, which has been extended to years prior to 1988 and four democracy measures to address differences among democracy indices. The results from a dynamic panel data model suggest that democracy's third wave decreased defense spending relative to GDP by about 10% within countries that experienced democratization. This result does not show to be heterogeneous across world regions which the third wave reached in different sub-waves. I exploit the regional diffusion of democracy in the context of the third wave of democratizations as an instrumental variable (IV) for democracy in order to overcome endogeneity problems. The IV estimates indicate that democracy decreased national defense spending relative to GDP by about 20% within countries, demonstrating that OLS results underestimate the effect of democracy on national defense spending. The cumulative long-run effect of democratization resulting from the dynamics in defense spending is almost three times higher for both OLS and IV estimates.
Keywords: H56; H41; C23; C26; D72; 330; defense spending; democracy; instrumental variable; panel data